Ultra‐Performance Liquid Chromatography Hyphenated with Quadrupole‐Orbitrap Mass Spectrometry for Simultaneous Determination of Necine‐Core‐Structure Pyrrolizidine Alkaloids in Crotalaria sessiliflora L. without all Corresponding Standards. Issue 5 (23rd March 2017) - Zhang, Wei; Huai, Wenbei; Zhang, Yi; Shen, Jincan; Tang, Xunyou; Xie, Xiujuan; Wang, Ke; Fan, Huajun
Abstract: Introduction: Crotalaria sessiliflora L. is a Chinese traditional herb for treatment of cutaneum carcinoma and cervical carcinoma. In addition to monocrotaline, coexisting pyrrolizidine alkaloids (PAs) also require further quantification for quality control and pharmaceutical uses of the herb. Objective: To establish a UPLC‐Q‐Orbitrap/MS method of simultaneous determination of coexisting PAs with same parent structure for quality control and comprehensive researches of Crotalaria sessiliflora L. Methodology: PAs in Crotalaria sessiliflora L. were analysed by UPLC‐Q‐Orbitrap/MS method. Coexisting PAs were identified by mass data of full MS‐dd‐MS 2 based on the characteristic fragmentation pattern and necine‐core structure. Moreover, quantification of PAs was conducted by parallel reaction monitoring (PRM) mode using m / z 138, m / z 120 and m / z 94 from identical necine‐core structure as quantitative ions with single monocrotaline standard for accurate calibration. Results: Five PAs, named monocrotaline, retrorsine, senecionine, integerrimine, O ‐9‐angeloylretronecine, were indentified and confirmed. Quantitative ions of m / z 138, m / z 120 and m / z 94 were used for quantification of PAs containing the necine‐core structure in Crotalaria sessiliflora L . The results demonstrated that contents, precision and recoveries of the five PAs mentioned earlier were respectively 3.307–30.35 μg/g, 1.1–4.5% and 88.91–92.33% while using m / z 120 as the best quantitative ion. Conclusion: The UPLC‐Q‐Orbitrap/MS method was established for simultaneous determination of five PAs in Crotalaria sessiliflora L. without all corresponding standards, and was proved that it was simple, convenient and effective for comprehensive quality control and pharmaceutical uses. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : A novel UPLC‐Q‐Orbitrap/MS method of simultaneous determination of five pyrrolizidine alkaloids (PAs) in Crotalaria sessiliflora L. was developed by UPLC‐Q‐Orbitrap/MS for quality control and pharmaceutical uses. Based on the characteristic fragmentation pattern, five coexisting PAs in the herb were identified by full MS‐dd‐MS 2 mode. Quantification of PAs successfully completed by parallel reaction monitoring mode using m/z 138, m/z 120 and m/z 94 from identical necine‐core structure as quantitative ions with single monocrotaline standard for accurate calibration.